EFFECT OF LATERAL HYPOTHALAMUS LESIONS ON THE WATER AND SALT INTAKE, AND SODIUM AND URINE EXCRETION INDUCED BY ACTIVATION OF THE MEDIAN PREOPTIC NUCLEUS IN CONSCIOUS RATS - Dasilva, RKP; Saad, W. A.; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP]; Camargo, LAD (Elsevier B.V., 1995)
In this-study we investigated the influence of electrolytic lesion of the lateral hypothalamus (LH) on the water and salt appetite, and the natriuretic, diuretic and cardiovascular effects induced by angiotensinergic, cholinergic and noradrenergic stimulation of the median preoptic nucleus (MnPO) in rats. Male Holtzman rats were implanted with a cannula into the MnPO. Other groups of sham- and LH-lesioned rats received a stainless steel cannula implanted into the MnPO. ANGII injection into the MnPO induced water and sodium intake, and natriuretic, diuretic, presser and tachycardic responses. Carbachol induced water intake, and natriuretic, presser and bradycardic responses, whereas noradrenaline increased urine, sodium excretion and blood pressure, and induced bradycardia. In rats submitted to LH-lesion only, water and sodium intake was reduced compared with sham rats. LH lesion also reduced the sodium ingestion induced by ANGII (12 ng) into the MnPO. In LH-lesioned rats, the dipsogenic, diuretic and presser responses induced by ANGII (12 ng), carbachol (2 nmol) and noradrenaline (20 nmol) injection into the MnPO were reduced. The same occurred with sodium excretion when carbachol (2 nmol) and noradrenaline (20 nmol) were injected into the MnPO of LH-lesioned rats, whereas ANGII(12 ng) induced an increase in sodium excretion. These data show that electrolytic lesion of the LH reduces fluid and sodium intake, and presser responses to angiotensinergic, cholinergic and noradrenergic activation of the MnPO. LH involvement with MnPO excitatory and inhibitory mechanisms related to water and sodium intake, sodium excretion and cardiovascular control is suggested.
Keywords: INGESTION; EXCRETION; ANGIOTENSIN II; CARBACHOL; NORADRENALINE